A review on rheological characteristics, serviceability and failure analysis of steel fiber impregnated concrete. (2022) - Vijayan, D.S.; Monisha, S.; Suneesh, S.; Vishak, M.; Sarathkumar, VS.
Abstract: Concrete technology is the application of science of proportioning economical and environmentally friendly concrete using readily available raw materials while meeting strength and durability criteria and workability constraints. It usually involves a thorough examination of the rheological characteristics, serviceability, failure analysis and elastic properties of concrete and its ingredients under a variety of conditions and combinations. Steel fibers are a kind of concrete reinforcement material that, when combined with concrete, offers many benefits over standard reinforcement. Steel fibers are manufactured from a variety of wire materials and are used to offer temperature and shrinkage crack control in concrete, enhanced flexural reinforcement, increased shear strength, and increased crack resistance.The article presents new research on the use of steel fibers in concrete, most likely in the year 2021, in order to educate readers on concrete technological advancements.